2010
DOI: 10.1080/00140130903389068
|View full text |Cite
|
Sign up to set email alerts
|

Endurance time is joint-specific: A modelling and meta-analysis investigation

Abstract: Static task intensity–endurance time (ET) relationships (e.g. Rohmert's curve) were first reported decades ago. However, a comprehensive meta-analysis to compare experimentally-observed ETs across bodily regions has not been reported. We performed a systematic literature review of ETs for static contractions, developed joint-specific power and exponential models of the intensity–ET relationships, and compared these models between each joint (ankle, trunk, hand/grip, elbow, knee, and shoulder) and the pooled da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
88
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 112 publications
(92 citation statements)
references
References 194 publications
4
88
0
Order By: Relevance
“…More recently, comparisons between several of these models observed that equations varied by joint region (El Ahrache et al, 2006; Ma et al, 2009; Ma et al, 2011). Likewise, a large meta-analysis of 194 publications involving experimental fatigue data confirmed joint-specific intensity-ET relationships (Frey Law and Avin, 2010). Thus, ETs vary as a function of task intensity, but also based on the joint region involved.…”
Section: Introductionmentioning
confidence: 81%
“…More recently, comparisons between several of these models observed that equations varied by joint region (El Ahrache et al, 2006; Ma et al, 2009; Ma et al, 2011). Likewise, a large meta-analysis of 194 publications involving experimental fatigue data confirmed joint-specific intensity-ET relationships (Frey Law and Avin, 2010). Thus, ETs vary as a function of task intensity, but also based on the joint region involved.…”
Section: Introductionmentioning
confidence: 81%
“…A comparison of the relationship between relative exertion level and endurance showed that the data reasonably followed the traditional form of a decreasing power function for both the obese and non-obese groups. (38,39) Previous work (18) on shoulder flexion endurance during sustained isometric tasks-which involved participants of similar age, stature, and BMI as here-indicated that the non-obese group had ∼20% longer endurance than the obese group.…”
Section: Effect Of Obesity On Functional Performancementioning
confidence: 90%
“…interpolated twitch techniques, then their relative-intensity target workload will be less than expected. A recent meta-analysis modeled endurance times as a function of task intensity for sustained isometric contractions at several joints (7). Using these models, the current 30 sec difference in endurance time observed between men and women at the elbow would require a difference in central activation of 14-16% between the sexes (e.g.…”
Section: Discussionmentioning
confidence: 99%